PRIMARY ACCOUNTING OF BUSINESS EXPENSES - ROMANOVA, OLGA; REPINA, SVETLANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article analyzes the process of documenting the costs of enterprises ’ activities. In the process of activity, enterprises bear a variety of costs in the production of necessary products for the functioning of production and non-production systems in the state, but the continuity of this process depends on the well-coordinated work of the energy complex, since energy consumers are all areas of the state economy that are set when forming GDP. Therefore, the importance of analyzing the composition of costs, production, financial, operational, and other types at energy enterprises is important, and given the gradual growth of the role of energy in the state economy, it is relevant. All expenses that are recorded in the company’s accounting records during the reporting period must be confirmed by documents characteristic of a certain group of expenses, so this particular direction was chosen for the study. The paper examined the existing features of the main primary documents for accounting for payroll accruals and payments, settlements with accountable persons, cash, material, and other expenses. In the process of writing the paper, the principle of filling out and containing 18 current documentary forms of the corresponding direction was described, divided into groups according to their purpose for a more visual display of the results of the study.